Answer:
[tex]\ln \frac{xy^2}{z}[/tex]
Step-by-step explanation:
Given expression:
[tex]\ln x+2\ln y-\ln z[/tex]
To write the given expression in single logarithm.
Solution:
We will apply the logarithm properties to write the expression in single logarithm.
We have:
[tex]\ln x+2\ln y-\ln z[/tex]
Using power rule : [ [tex]a\ln b= \ln b^a[/tex] ]
⇒ [tex]\ln x+\ln y^2-\ln z[/tex]
Using product rule: [ [tex]\ln a+\ln b=\ln ab[/tex] ]
⇒ [tex]\ln xy^2-\ln z[/tex]
Using quotient rule. [ [tex]\ln a - \ln b = \ln\frac{a}{b}[/tex] ]
⇒ [tex]\ln \frac{xy^2}{z}[/tex]
Thus, we successfully converted the expression to a single logarithm expression.